2003
DOI: 10.1001/archneur.60.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Alzheimer Disease in a Biracial Urban Community

Abstract: Apolipoprotein E epsilon4 led to increased risk of AD among white subjects but not black subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
286
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 327 publications
(301 citation statements)
references
References 26 publications
13
286
1
1
Order By: Relevance
“…59,60 Other studies found interaction effects of APOE with environment and diet depending on ethnicity or country of origin. 36,[61][62][63][64] To further confuse the situation, some of these studies compared US populations with communities in other countries, making findings difficult to generalize to African Americans. They also failed to adjust for the ages of research participants or account for competing risks of death.…”
Section: Contribution Of Apoe Genotype To Ad Risk Among African Amerimentioning
confidence: 99%
“…59,60 Other studies found interaction effects of APOE with environment and diet depending on ethnicity or country of origin. 36,[61][62][63][64] To further confuse the situation, some of these studies compared US populations with communities in other countries, making findings difficult to generalize to African Americans. They also failed to adjust for the ages of research participants or account for competing risks of death.…”
Section: Contribution Of Apoe Genotype To Ad Risk Among African Amerimentioning
confidence: 99%
“…We obtained incidence data from the Chicago Health and Aging Project (CHAP), 3,4 a longitudinal, populationbased study in a geographically defined area of Chicago. The study began in 1993 with a census of individuals aged 65 years or older.…”
mentioning
confidence: 99%
“…Homozygosity with respect to the E4 allele increases the risk of Alzheimer disease by a factor of 33 in Japanese, 15 in European Americans and 6 in African Americans 53 . A more recent study also found differential effects of the E4 allele between Europeans Americans and African Americans 54 . It is impossible to determine from current evidence whether these differences reflect an interaction of APOE with genetic background or with environment.…”
Section: Genetic Subclassification Of Diseasementioning
confidence: 81%